(untitled) (Global Journals of Research in Engineering, 2012)
In the current competitive business environment many factors can influence on firms Survival, but the most important factors those senior managers focus are service quality, customer`s satisfaction and cash flow, it is aimed to simulate these factors in a company. In most situation a company have good amount of potential customers who order for the first produce line, but inventory is not enough to answers all orders, hence back orders and lost orders comes up. Lost orders will effects on market and companies market share directly, back orders will gradually effect on companies market share and directly play a role on supply chain planning. On the other hand products price will cause a big change on orders which effects on income. And presumably the annual expenses and tax will change. This illustrates the Company cash flow and the credit which it can invest on getting loans. In this paper, it is tried to simulate all this parts, therefore the model is formed of three parts: customers satisfactory, orders and service quality and cash flow.